Adult education students perceptions of e-learning: a case study of Midlands State University. - Chitanana, Lockias; Museva, Loveness (Midlands State University, 2016)
This paper examines Adult Education Students perceptions of e-learning at Midlands State University in Zimbabwe. Considering students perceptions toward e-learning is important in successful development of e-learning in higher education since perception of users towards application of information technology is one of the most effective factors of technology integration. A descriptive survey approach was used in this study. Adult Education students (n = 24) participated in the study. Reliability and validity of instruments were determined in consultation with e-learning specialists at Midlands State University and application of Cronbach s Alpha (á=0.88.) Descriptive statistics were used to analyze the data using SPSS version 13. Results indicate that students have a positive perception of E-Learning as it enhances their learning and facilitates communication and interaction between fellow students and between lecturers and students, a means to access additional information to supplement the course content.